Experimental realization of nonadiabatic holonomic single‐qubit quantum gates with two dark paths in a trapped ion - Ming-Zhong Ai; Sai Li; Ran He; Zheng-Yuan Xue; Jin-Ming Cui; Yun-Feng Huang; Chuan-Feng Li; Guang-Can Guo (Fundamental Research, 2022)
For circuit-based quantum computation, experimental implementation of a universal set of quantum logic gates with high-fidelity and strong robustness is essential and central. Quantum gates induced by geometric phases, which depend only on global properties of the evolution paths, have built-in noise-resilience features. Here, we propose and experimentally demonstrate nonadiabatic holonomic single-qubit quantum gates on two dark paths in a trapped 171Yb+ ion based on four-level systems with resonant drives. We confirm the implementation with measured gate fidelity through both quantum process tomography and randomized benchmarking methods. Meanwhile, we find that nontrivial holonomic two-qubit quantum gates can also be realized within current experimental technologies. Compared with previous implementations, our experiments share both the advantages of fast nonadiabatic evolution and robustness against systematic errors. Therefore, our experiments confirm a promising method for fast and robust holonomic quantum computation.